Conhecendo um pouco sobre otimização : do ensino médio ao ensino avançado - Silva, Marcelo Ricardo Santos da (2018)
In this work we show contents of high-school and college which can be applied when the subject is to optimise. The search for the great is something very present in our lives. Different areas, amongst them, Operational Reserach, search for better solutions for their problems. For example, the best way to distribute scarce resources among the sectors of an industry. Studying optimisation may sharpen in people the interest for studying Mathmatics, and the understanding that the squaring function is not the only way of modeling and solving problems of optimisation.